OBTENÃ‡ÃƒO DE UM FUNGO COM ALTO PODER HIDROLÃTICO SOBRE BAGAÃ‡O DE CANA PRÃ‰ TRATADO - Vitti, L. S. S.; Silva, D. M.; Vitti, D. M. S. S. (REVISTA DE AGRICULTURA, 2015)
OBTENÃ‡ÃƒO DE UM FUNGO COM ALTO PODER HIDROLÃTICO SOBRE BAGAÃ‡O DE CANA PRÃ‰ TRATADO